Hull cell cutting device and hull cell cutting system - LYU XUEFENG; XIONG DASHUN; YU FEI; GONG FEN (2018)
The utility model provides a hull cell cutting device and hull cell cutting system relates to hull cell cutting technical field. This hull cell cutting device includes transmission unit, positioning system, cutting unit and collector unit. The cutting unit includes crosscut unit and rip cutting unit, and the crosscut unit is used for cutting for the first time the hull cell, and the rip cutting unit is used for cutting for the second time the hull cell. This hull cell cutting device can roll up CIGS flexible thin -film battery and be processed into the CIGS standard cell who can be used to stitch welding production, cut efficient, the cutting accuracy height. The utility model provides a hull cell cutting system, including the control unit and foretell hull cell cutting device, degree of automation is high, has improved cutting efficiency greatly. 本实用新型提供的薄膜电池切割装置和薄膜电池切割系统，涉及薄膜电池切割技术领域。该薄膜电池切割装置包括传输单元、定位系统、切割单元和收集单元。切割单元包括横切单元和纵切单元，横切单元用于第次切割薄膜电池，纵切单元用于第二次切割薄膜电池。该薄膜电池切割装置可将CIGS柔性薄膜电池卷加工成可用于叠焊生产的CIGS标准电池，切割效率高